IMPLEMENTATION OF RESTORATIVE JUSTICE SYSTEM FOR DRUG ABUSERS - Shalasa, Idham Malik; Subekti; Suyono, Yoyok Ucuk; Prawesthi, Wahyu (jfpublisher, 2023)
Nowadays, narcotics and drug crimes have been transnational crime that conducted with sophisticated technology. Then, law enforcement officials are expected to prevent and solve these crimes in order to improve the morality and quality of human resources in Indonesia, especially for the nation’s next generation. Therefore, this research aims to find out the implementation of restorative justice systems for drug abusers in Indonesia. This research is a normative juridical approach. The normative juridical approach is to use legislation, examine all laws and regulations related to the legal issues. The restorative justice approach can only be applied to addicts, abusers, victims of abuse, drug dependence, and one-day narcotics use, as stipulated in Article 1 of Joint Decree of Chief Justice of Supreme Court, Minister of Law and Human Rights, Minister of Health, Minister of Social Affairs, Attorney General, Chief of Police, Head of National Narcotics Agency Number 01/PB/MA/111/2014, No. 03/2014, No. 11/2014, No. 03/2014, Number Per 005/A/JA/03/2014, No. 1/2014, Number Perber/01/111/2014/BNN on Handling Narcotics Addicts and Victims of Narcotics Abuse into Rehabilitation Institutions.